CASE REPORT Leigh disease: 9 years follow up of a Polish family harboring T8993C mitochondrial DNA mutation - Kisiel, Bartłomiej; Korniszewski, Lech; A. Małek, Łukasz (Archives of Medical Science, 2005)
Leigh disease (LD) or subacute necrotizing encephalomyelopathy (SNE) is a mitochondrial dysfunction. It can be caused by either mitochondrial or nuclear DNA mutations, which impair communication of the complexes of the human electron transporting chain (ETC) directly or by interfering with nucleus-mitochondrion. Leigh disease is characterized by psychomotor retardation, muscle weakness, pyramidal signs, lactic acidosis, hypotonia, dysphagia, symmetric basal ganglia and brainstem lesions. Due to a relatively small number of published cases and multisystemic involvement of LD there is no clear definition of symptoms and definite diagnosis can be based only on the genetic analyses. In our study we describe a Polish family harboring T8993C mutation in one of the subunits of ETC complex V (ATPase). We present the differential diagnosis of LD and observations of the described family performed 9 years from the diagnosis of Leigh disease. We suggest that the results of the neurophysiologic examinations in LD patients are characteristic both for neuronal and muscular lesions. Apart from that we assessed physical or psychological state of the family members measured by self-constructed LD-specific quality of life questionnaire.